Plasminogen Activator Inhibitor 1 Is Elevated in the Children of Men with Premature Myocardial Infarction - Rallidis, Loukianos S; Megalou, Ageliki A; Papageorgakis, Nikos H; Trikas, Athanasios G; Chatzidimitriou, Grammatiki I; Tsitouris, George K (Thrombosis and Haemostasis, 1996)
To assess whether plasminogen activator inhibitor 1 (PAI-1) activity is elevated in the progeny of young coronary men, 193 young subjects were recruited and divided into two groups. Group A consisted of 104 children whose fathers had suffered a myocardial infarction before the age of 55 (“cases”). Eighty-nine young subjects matched for age, sex, body mass index (BMI) and smoking habits without familial history of coronary artery disease (CAD) served as controls (group B). Children with a family history of diabetes mellitus or hypertension were excluded from both groups. We measured PAI-1 activity, tissue-type plasminogen activator (t-PA) antigen, a2-antiplasmin, fibrinogen, lipids and apolipoproteins in both groups. PAI-1 activity levels were also determined in the men who suffered a premature myocardial infarction 4 months after their discharge. PAI-1 activity levels were higher in cases compared to controls (3.13 ± 1.9 vs 2.17 ± 1.9 U/ml, p = 0.0014). t-PA antigen and a2-antiplasmin did not differ significantly between the two groups, while fibrinogen, total cholesterol, low-den-sity lipoprotein cholesterol, apolipoprotein B and lipoprotein(a) were significantly higher in group A. PAI-1 was positively correlated with triglycerides (r = 0.22, p = 0.024), apolipoprotein B (r = 0.21, p = 0.039) and fibrinogen (r = 0.22, p = 0.029 ) in cases and with BMI in both cases (r = 0.37, p = 0.0003) and controls (r = 0.23, p = 0.044). In stepwise multiple regression analysis, only apolipoprotein B (p = 0.008) and BMI (p = 0.0014) were significant determinants of PAI-1 activity in cases. There was also a positive correlation between PAI-1 activity levels of the affected fathers and their children (r = 0.30, p = 0.01). The present data support the hypothesis that elevated PAI-1 levels in the offspring of men with premature myocardial infarction impair their fibrinolytic capacity contributing to their familial predisposition to CAD.